Multilayer Mirror Based High-Resolution Solar Soft X-Ray Spectrometer - Panini, S. S.; Narendranath, S.; Sreekumar, P.; Sankarasubramanian, K. (Frontiers in Astronomy and Space Sciences, 2021)
Soft X-ray spectroscopy of the Sun is an important tool to understand the coronal dynamics and composition. The solar coronal X-ray spectrum below 1 keV is the least explored with high-resolution spectroscopy. Recent observations with Hinode XRT using coarse spectroscopy along with high-resolution imaging have shown that abundances in the coronae have variability associated with structures on the Sun. Disk averaged abundances with better spectral resolution spectrometers show time variability associated with flares. Both spatial and temporal variabilities seem to be related to changes in the magnetic field topology. Understanding such short term variabilities is necessary to model the underlying dynamics and mixing of material between different layers of the Sun. A Sensitive high-resolution spectrometer that covers the range in plasma temperatures and emission line complexes would uniquely reveal the entire evolution of flares. We are investigating a design of a multi-layer mirror-based X-ray spectrograph in the spectral range from 0.5-7 keV. The instrument operates in 4 asynchronous spectral channels operating one at a time. The multi-layer mirror placed at the focus of a Wolter type I telescope reflects a narrow band X-rays to the CCD which is placed at Nasmyth defocus. Converging X-rays from the front end optics helps to increase the spectral range of each channel while preserving the spectral resolution. This design is estimated to achieve a spectral resolution of 20 eV in the spectral range of 0.5-7 keV. With such high spectral resolution, we can resolve individual spectral features e.g., 6.7 keV Fe complex which can be used to diagnose high-temperature transient plasma during flares. The instrument design estimated performance and the science capabilities of this instrument will be discussed in detail in the paper.